The influence of risk factors in patients with ulcer disease on the duration and multiplicity of the treatment in residents of Vinnytsia region - Kizlova, Nataliia; Komar, Olena; Trylevych, Oleksandra (ScienceRise: Medical Science, 2018)
The aim of the study is to reveal the influence of the risk factors in patients with gastric and duodenal peptic ulcer on duration and multiplicity of the treatment in residents of Vinnytsia region. Methods. As the materials for research we used reporting forms from Vinnitsia state medical institutions: inpatient cards 003/0, outpatient cards 025/0 ( total n=700 with duodenal and gastric ulcer), cards of patients who left the hospital, questionnaires. In order to calculate the dependence between the risk factors and duration and multiplicity of treatment thereof we used the criteria of score valuation of the Charlson index, which accumulates the comorbidity of diseases. Result. The results of quantitative evaluation of the factors scoring suggest of the underlying H.pylori infection (the significance of which is growing along with the growth of the disease incidence) and comorbidity as the most important ones. There is a linear dependence between the risk factors and the necessity for specialized care, which was manifested in the duration and multiplicity of treatment. Conclusions. We have established the direct dependence between the most important peptic ulcer risk factors, severity of the disease, and duration and periodicity of treatment thereof during the year in the day gastroenterological hospital. We revealed the necessity for formation of risk groups among the population, each of which requires a systematic approach to studying the general condition, taking into account existing illnesses, their negative interactions. The best method of improving the medical care organization is active-constructive prophylaxis